S-Layer Protein of Lactobacillus helveticus SBT2171 Promotes Human β-Defensin 2 Expression via TLR2–JNK Signaling - Kobatake, Eiji; Kabuki, Toshihide (Frontiers in Microbiology, 2019)
Antimicrobial peptides that contribute to innate immunity are among the most important protective measures against infection in many organisms. Several substances are known to regulate the expression of antimicrobial peptides. In this study, we investigated the factors in lactic acid bacteria that induce antimicrobial peptide expression in the host. We found that Lactobacillus helveticus SBT2171 (LH2171) induced the expression of human β-defensin (hBD)2 in Caco-2 human colonic epithelial cells. Specifically, surface layer protein (SLP) of LH2171 stimulated hBD2 expression by activating c-Jun N-terminal kinase (JNK) signaling via Toll-like receptor (TLR)2 in Caco-2 cells. SLPs extracted from other lactobacilli similarly increased hBD2 expression, suggesting that this stimulatory effect is common feature of Lactobacillus SLPs. Interestingly, Lactobacillus strains that strongly induced hBD2 expression also potently activated JNK signaling. Thus, upregulation of hBD2 induced by TLR2–JNK signaling contributes to protection of the host against infection.